2006
DOI: 10.3748/wjg.v12.i17.2694
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment of functional dyspepsia

Abstract: the role of Helicobacter pylori (H pylori ) in functional dyspepsia continues to be a matter of debate, recent data indicate that there is modest but clear benefit of eradication of H pylori in patients with functional dyspepsia. In addition, H pylori is a gastric carcinogen and if found it should be eliminated. Although there are no specific diets for patients with FD, it may be helpful to guide the patients on healthy exercise and eating habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 63 publications
1
21
0
3
Order By: Relevance
“…Moreover, the analgesic action of this drug could be beneficial for functional dyspepsia patients whose threshold level of visceral sensitivity is lower (visceral hypersensitivity) compared to that of healthy subjects. [15][16][17] Our study showed that amitriptyline and placebo were equally excellent for functional dyspepsia treatment, as both amitriptyline and placebo decreased the frequency and duration of functional dyspepsia. However, there were no significant differences in frequency or duration after treatment between the amitriptyline and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the analgesic action of this drug could be beneficial for functional dyspepsia patients whose threshold level of visceral sensitivity is lower (visceral hypersensitivity) compared to that of healthy subjects. [15][16][17] Our study showed that amitriptyline and placebo were equally excellent for functional dyspepsia treatment, as both amitriptyline and placebo decreased the frequency and duration of functional dyspepsia. However, there were no significant differences in frequency or duration after treatment between the amitriptyline and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…It involves many pathogenic factors and different pathophysiological disturbances, including delayed gastric emptying, impaired accommodation, and hypersensitivity to gastric distention. Treatment of the underlying pathophysiological abnormality seems logical, but the main pharmacotherapeutic options include acid suppression, prokinetic drugs, and antidepressants [6,[24][25][26], all of which have limited effects. Herbal formulations are widely used to treat FD in China and many other areas in the world.…”
Section: Discussionmentioning
confidence: 99%
“…Lebensjahr sowie beim Auftreten von Alarmsymptomen (Anämie, Dysphagie, persistierendes Erbrechen, familiäre Belastung, Fremdkör-pergefühl). Bei den anderen Patienten ist zunächst ein Therapieversuch mit einem Protonenpumpenhemmer (PPI) über 4-8 Wochen indiziert [44]. Ebenfalls sollte bei diesen Patienten eine nichtinvasive Helicobacter-pylori-Testung, zum Beispiel mittels C 13 -Atemtest, erfolgen.…”
Section: Wie Wird Die Funktionelle Dyspepsie Diagnostiziert?unclassified
“…Funktionsuntersuchungen wie die pHMetrie, Manometrie oder Impedanzmessung spielen bei der Diagnose der FD keine Rolle [44].…”
Section: Wie Wird Die Funktionelle Dyspepsie Diagnostiziert?unclassified